2020
DOI: 10.1016/j.arrct.2020.100089
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patterns, and Predictors of Multimorbidity in Adults With Acquired Brain Injury at Admission to Staged Community-Based Rehabilitation

Abstract: Objectives To describe the prevalence, patterns, and predictors of multimorbidity in adults with an acquired brain injury (ABI) on presentation to a community-based neurorehabilitation service. Design Retrospective cohort study using routinely collected admissions and clinical data. Setting Community-based neurorehabilitation. Participants Individuals (N=263) with non-traumatic brain injury (NTBI; n=187 [71.1%]) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Participants were generally male (71%), married or in a de facto relationship (46%) and held full- or part-time employment before their injury (68%). These age [ 43 , 44 ], gender [ 43 , 44 ] and employment [ 45 ] rates are typical of a brain injury population, however, there was a higher proportion of participants who were married or in a de facto relationship than what might be expected [ 46 ]. Severe traumatic injuries were most common (61%) and the median length of hospital stay was 47 days—both slightly higher than what might be expected of an Australian sample [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were generally male (71%), married or in a de facto relationship (46%) and held full- or part-time employment before their injury (68%). These age [ 43 , 44 ], gender [ 43 , 44 ] and employment [ 45 ] rates are typical of a brain injury population, however, there was a higher proportion of participants who were married or in a de facto relationship than what might be expected [ 46 ]. Severe traumatic injuries were most common (61%) and the median length of hospital stay was 47 days—both slightly higher than what might be expected of an Australian sample [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…These age [ 43 , 44 ], gender [ 43 , 44 ] and employment [ 45 ] rates are typical of a brain injury population, however, there was a higher proportion of participants who were married or in a de facto relationship than what might be expected [ 46 ]. Severe traumatic injuries were most common (61%) and the median length of hospital stay was 47 days—both slightly higher than what might be expected of an Australian sample [ 46 ]. As expected, [ 46 ] 27% of participants had no comorbidities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBR is focused on approaches that are developed in low-resource, capacity-constrained settings, especially LMICs (WHO, 2010). However, this term has been used throughout the literature to be synonymous with CBI within or outside the context of the CBR programme itself, whether it is developed within high-income countries (Bettger et al, 2019;Graven et al, 2011;Handberg, Mygind, & Johansen, 2019;Jackson, Troeung, & Martini, 2020;Jeong & Kim, 2007) or low-and middle-income countries (Iemmi et al, 2015;Yan et al, 2016).This makes searching for CBIs applicable to LMICs a tedious process.…”
Section: Discussionmentioning
confidence: 99%
“… 41 43 Prior research using a retrospective convenience sample of 263 ABI-RESTaRT members admitted to the service from 2009 to 2018 found that mental health comorbidities were present in 55.8% of the sample (n=106), representing the most common comorbidity. 44 ABI-RESTaRT provides the opportunity to examine the prevalence of mental illness, specific mental health needs and its impact on rehabilitation outcomes to inform policy and services for mental health and ABI.…”
Section: Future Directionsmentioning
confidence: 99%